Dynamized ethyl alcohol improves immune response and behavior in murine infection with Trypanosoma cruzi. (November 2017) - Sandri, Patrícia F.; Portocarrero, Angela R.; Ciupa, Larissa; Ferraz, Fabiana N.; Falkowski-Temporini, Gislaine J.; Rodrigues, Willian N.S.; Ferreira, Érika C.; Aleixo, Denise L.; de Araújo, Silvana Marques
Graphical abstract: Highlights: Beneficial effect of Ethylicum 6cH in acute murine infection by T. cruzi. Ethylicum 6cH presented pronounced Th2 response. Ethylicum 6cH decreased inflammation in heart and increased host's survival. Ethylicum 30cH exhibited pronounced Th1 response. Abstract: Aim: To evaluate the effects of dynamized ethyl alcohol ( Ethylicum) 6cH and30cH in mice infected with T. cruzi. Methods: In a blind, randomized and controlled assay, 63 eight-week-old, Swiss, male mice, infected with IP (1400 trypomastigotes, T. cruzi -Y-strain), were allocated into groups:CNI -non-infected (n = 12), CI -infected and non-treated (n = 17), Et6cH -infected, treated with Ethylicum 6cH (dilution 1:10 12 ) (n = 17), Et30cH -infected, treated with Ethylicum 30cH (dilution 1:10 60 ) (n = 17). Treatment was administered 48 h before and after infection, followed by 56 h/56 h periods, until the 9th day after infection (a.i), for 16 h. Survival and mortality were assessed until the 82nd day after infection (a.i.). TNF-α, IL-6, IL-10, IL-5 and IL-17A cytokines were assessed in serum (3–4 animals/group), at time T0 (before infection), T8 and T12 (8th and 12th a.i), using the Mouse Cytokine 20-Plex Panel Magnetic Kit (Invitrogen, USA). Inflammation was determined in heart sections (eosin-hematoxylin staining) and behavior was analyzed with ANY-maze® software. The study was approved by the Animal Ethics Committee/UEM. Statistica 8.0 and R 3.0.2 software were used for statistical analyses. Results: The greater survival observed in theEt6cH group was related to decreased inflammation in heart tissue and increased IL-5 at T0 (p < 0.05) and IL-10 at T8 (p < 0.05), characterizing the Th2 response. It was also related to shorter periods of immobility, observed on day 12 a.i. The higher mortality in theEt30cH group was related to increased inflammation in the heart and a higher concentration of IL-6 and TNF-α cytokines, characterizing the Th1 response. Conclusion: The results demonstrate the beneficial effect of Ethylicum 6cH in acute murine infection by T. cruzi .